(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background and Objective: This study was designed to evaluate clinically and radiographically the role of Ozonated olive oil in the management of periodontal status in smoking patients. Materials and Method: The study was performed on twenty four medically free patients having chronic periodontitis. Radiographic bone density evaluation as well as linear alveolar bone level and clinical periodontal parameters were recorded after the initial phase of plaque control then, the patients were instructed to perform oral hygiene measures. The clinical parameters which were included are; plaque index, gingival index, probing depth and clinical attachment loss. The patients were divided into 2 main groups, the first group received Ozonated olive oil while the second group served as control group. At baseline, three and six months, bone density and alveolar bone level were radiographically recorded using CBCT. The statistical analysis of the collected clinical and radiographic data revealed an overall clinical as well as Radiometric and Densitometric measurements improvement by time for the Ozonated olive oil group in comparison to the control group at baseline, three and six months. Results: Ozonated olive oil group showed significant difference regarding the control group. Conclusion: The results of the current study revealed that the use of Ozonated olive oil can enhance bone level and density as well as tissue healing in periodontially affected teeth. In addition, the use of CBCT is considered as an effective method for evaluation of preoperative and postoperative alveolar bone.